Identification of Six Sigma Methodology in Fisheries Production Process Can Improve Product Quality Based on Blue Economic Prospectives - Muhammad Alva Roby; Toto Iswanto (MJK PUBLISHER, 2024)
The achievement of national fisheries production of 18.5 million tons until the third quarter of 2023 reflects the great potential that Indonesia has in optimizing the use of its marine resources. The blue economy approach offers a sustainable growth model, utilizing marine resources wisely to improve human welfare without damaging the marine ecosystem. This study aims to identify how the Six Sigma methodology in the fisheries production process can improve product quality based on the prospective blue economy at PT. XYZ, a crab processing company in Sidoarjo, East Java. The main objective of this study is to evaluate the impact of Six Sigma implementation on product quality and the company's operational efficiency. The research methods used include case studies, analysis of production data and defect rates, and interviews with company management. The results of the study showed a significant increase in product quality, with a decrease in the defect rate from an average of 3.40% before implementation to 1.68% after implementation.